Application of Pre-training Model in Natural Language Processing - Chu, Zhaosicheng (Transactions on Computer Science and Intelligent Systems Research, 2025)
Natural language processing is a very important research area in the field of artificial intelligence, with the goal of enabling computers to understand human language, this research area brings together information from multiple disciplines such as linguistics, computer science, machine learning, mathematics, and cognitive psychology, it has two sides: cognition and understanding of natural language and natural language processing. Of these, natural language recognition and understanding allow computers to represent meaningful and quantifiable symbols and relationships in input language and compute accordingly depending on tasks. Natural language processing activities include the construction of models that explain language abilities and language applications, the creation of computational mechanisms for implementing and improving language models, the design of usage systems from language models, and the exploration of evaluation methods for such systems. This article elaborates on the conceptual framework of pre training models and discusses three mainstream pre training language architectures. Through comparative experiments with multiple indicators, this article verifies the excellent performance of pre trained models in natural language processing, which has significant advantages compared to traditional methods. Finally, the current status and future prospects are summarized.